Host-Dependent Producibility of Recombinant Cypridina noctiluca Luciferase With Glycosylation Defects - Mitani, Yasuo; Yasuno, Rie; Kihira, Kiyohito; Chung, KwiMi; Mitsuda, Nobutaka; Kanie, Shusei; Tomioka, Azusa; Kaji, Hiroyuki; Ohmiya, Yoshihiro (Frontiers in Bioengineering and Biotechnology, 2022)
Cypridina noctiluca luciferase (CLuc) is a secreted luminescent protein that reacts with its substrate cypridinid luciferin to emit light. CLuc is known to be a thermostable protein and has been used for various research applications including in vivo imaging and in high-throughput reporter assays. Previously, we produced a large amount recombinant CLuc for crystallographic analysis. However, this recombinant protein did not crystallize, probably due to heterogenous N-glycan modifications. In this study, we produced recombinant CLuc without glycan modifications by introducing mutations at the N-glycan modification residues using mammalian Expi293F cells, silkworms, and tobacco Bright Yellow-2 cells. Interestingly, recombinant CLuc production was highly dependent on the expression hosts. Among these selected hosts, we found that Expi293F cells efficiently produced the recombinant mutant CLuc without significant effects on its luciferase activity. We confirmed the lack of N-glycan modifications for this mutant protein by mass spectrometry analysis, but found slight O-glycan modifications that were estimated to be about 2% of the ion chromatogram peak area for the detected peptide fragments. Furthermore, by using CLuc deletion mutants during the investigation of O-glycan modifications, we identified amino acid residues important to the luciferase activity of CLuc. Our results provide invaluable information related to CLuc function and pave the way for its crystallographic analysis.